Bilateral aldosterone suppression and its resolution in adrenal vein sampling of patients with primary aldosteronism: analysis of data from the WAVES‐J study. (19th May 2016) - Shibayama, Yui; Wada, Norio; Umakoshi, Hironobu; Ichijo, Takamasa; Fujii, Yuichi; Kamemura, Kohei; Kai, Tatsuya; Sakamoto, Ryuichi; Ogo, Atsushi; Matsuda, Yuichi; Fukuoka, Tomikazu; Tsuiki, Mika; et al.
Summary: Context: In adrenal vein sampling (AVS) for patients with primary aldosteronism, the contralateral ratio of aldosterone/cortisol (A/C) between the nondominant adrenal vein and the inferior vena cava is one of the best criteria for determining lateralized aldosterone secretion. Despite successful cannulation in some patients, the A/C ratios in the adrenal veins are bilaterally lower than that in the inferior vena cava (bilateral aldosterone suppression; BAS). Objectives: To investigate the prevalence of BAS in AVS and how to resolve this condition. Design and setting: Retrospective study involving nine referral centres. Patients: Four hundred and ninety‐one patients who were confirmed as having primary aldosteronism and had an AVS between January 2006 and December 2013. Measurements: The prevalence of BAS before and after ACTH stimulation was compared. In addition, we investigated other methods for overcoming BAS. Results: In 304 patients with successful AVS before ACTH stimulation, BAS was observed in 29 (9·5%). BAS was resolved after ACTH stimulation in 22 patients. In 276 patients with successful AVS both before and after ACTH stimulation, the frequency of BAS was significantly reduced after ACTH (8·7% vs 2·5%, P < 0·01). In a few patients, BAS was also resolved by adding a sampling point at the common trunk of the left adrenal vein and by an alternative drainage vein from the adrenal tumour. Conclusions: BAS sometimes occurs in AVS without ACTH stimulation. ACTH stimulation significantly reduces BAS with a single AVS procedure.